The Federal Law of March 7, 2011 № 26-ФЗ in action - Natalya Nikolaevna Saleva (Сибирское юридическое обозрение, 2011)
The author considers problems that courts encounter dealing with motions of convicts to bring the existing sentences with compliance the Criminal Law in the context of the Federal Law № 26-FZ adopted on March 7, 2011. The article deals with the most problematic situations of qualifying and punishing individuals who are currently serving or have served their terms in accordance with verdicts.